Potential Loss among Infant Feeding Options - Azniah Syam; Musni Musni; Andi Nurzakiah Amin; Imelda Iskandar (Universitas Airlangga, 2021)
Introduction: The conceptual relationship between economics and breastfeeding is still mathematically invaluable, while the family's economic burden increases along with babies born. Indicating potential loss when a family chooses other than breastmilk is a progressive way to manage campaign messages about exclusive breastmilk and prolonged breastfeeding. Descriptive studies are needed to magnify all of these indicators and transform them into measuring instruments generalized to assess family expenditures related to infant feeding.Methods: This study uses a quantitative descriptive design, questionnaire draft upon qualitative open questions containing all micro indicators impacted financially during the baby’s first year. Data collection was carried out in Makassar based on telephone surveys with 330 preliminary samples. After structural analysis and data reduction, the expenditure indicators were divided into medical and non-medical expenses.Results: The study show there is a difference in the average amount of family expenses of those who provide formula milk compared to breastmilk. This outcome is 21.1 times higher in non-medical components and 2.5 times higher in the medical component. One of the highest contributions in medical expenses is the cost of a recurrent visit to a pediatrician due to a history of illness such as allergies, respiratory infections, and diarrhea.Conclusion: This empirical fact stated the strong affirmation of how families should consider wisely to choose the best feeding pattern for babies aged 0-12 months.